Cesarean Delivery Profile in a Military Hospital of Bangladesh- A Retrospective Study (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Background: In recent years there have been substantial increases in the cesarean delivery [CD] rates in Bangladesh.Objectives:With this background, a study was undertaken to describe cesarean delivery rate, indication of cesarean delivery, health outcome of mother and newborn attributed to the procedre.Methods: This retrospective chart review study [the period from February 1, 2014 to January 31, 2015] was carried out at Military Hospital of Bangladesh with the approval of the Institutional Ethics Committee. CD rates were computed by several maternal and newborn characteristics including maternal age, neonatal birth weight and parity. Three categories were used for maternal age: less than 18 years, 18-34 years, and 35 or older. Three groups were also used for neonatal birth weight: less than 2499 grams (low birth weight), 2500-3999 grams, and 4000 grams or more (macrosomia). Parity was divided into two groups: primiparas and multiparas. Main indication for caesarean delivery was also collected from operation list submitted by the obstetricians. Types of surgery [e.g. emergency or elective] were also evaluated.Results: During the aforementioned period of time there were 617 deliveries, which included 166 normal vaginal deliveries (NVD) and 451 CD. There were two intrauterine fetal deaths. Two hundred and seventy two patients underwent primary CD (i.e. with no history of previous cesarean section). There was exclusion of 23 deliveries [lack of records]. Thus study population consisted of 594 women and their newborns. Cesarean delivery rate obtained for the period studied was 72.05% (428/594), with primary CD rate being 62.10% (272/438).Conclusions: We conclude that the incidence of CD at our hospital is too high. Further studies are needed to provide clear answers as to the causes [etiologies] of this trend.JBSA 2016; 29(2): 39-44